Genetic Analysis of Morpho-Physiological Characteristics of Sunflower Under Stress and Non-Stress Drought Conditions - Mehdi Zohdi Aghdam; Farrokh Darvish Kojouri; Mehdi Ghaffari; Asa Ebrahimi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Five Cytoplasmic Male Sterility (CMS) lines and four restorer lines (tester) were crossed in a line x tester scheme in order to analyze general and specific combining abilities and gene effects on sunflower for some agronomic and physiologic traits. Hybrids were evaluated in a randomized complete block design, with three replications under optimum and limited water conditions. The results of combined analysis of variance for different traits in optimal conditions showed that the mean square, except for the % RWC traits in the limited conditions for plant height, head diameter, number of seeds per head, 1000-seeds weight, proline, catalase enzyme, superoxide dismutase enzyme, chlorophyll a, chlorophyll b, grain yield, and oil yield were significant. Results of data variance analysis indicated that the general combining ability for lines and tester was significant, as well as the specific combining ability (line x tester) for most traits. Based on the AGHK30 and AGHK44 combining ability, the RGHK25, RGHK50 and RGHK50 x AGHK56 and the RGHK56 x AGHK44 tester were identified as the most suitable line for the hybrid test in both conditions.